Cleaning Up : How Hospital Outsourcing Is Hurting Workers and Endangering Patients - Dan Zuberi (Cornell University Press, 2013)
Tracy Melucci cleans a hospital for a living.1 Well, sometimes clean is a strong word. More realistically, she makes her hospital less dirty than it was before. Short on time, short on resources, and long on responsibilities, she cleans what she can. And she knows itâ€™s not enough. â€œBasically, you do the big stuff and then you start cutting corners,â€ she says. â€œYou just cannot get it all done. And when I say â€˜cutting cornersâ€™ that means bathrooms, offices, hallways. Stuff gets missed.â€ Stuff gets missed. Hospitals across the United States, Canada, and much of Europe have dramatically changed their approach to housekeeping and other support work in the last decade, and people are dying as a result. Disinvestment and outsourcing of hospital cleaning services have left hospitals less hygienic and more vulnerable to the spread of hospital-acquired infections.